Gleasonian structure in the helminth metacommunity of the opossum Didelphis albiventris in two extremes of the Atlantic Forest. (28th January 2022) - Cirino, B.S.; Costa-Neto, S.F.; Cardoso, T.S.; Estrela, P.C.; Maldonado, A.; Gentile, R.
Abstract: Didelphis albiventris is the opossum with the largest geographic distribution in Brazil and has a wide spectrum of helminth parasites. This study aimed to describe the species composition and analyse the structure of helminth communities of D . albiventris in two extremes of the Atlantic Forest in Brazil. The influence of host sex, body mass, age, helminth species richness and locality on the abundance and prevalence of the most prevalent helminth species was investigated. Ninety-five per cent of the animals were infected with at least one species. Nine helminth species were found: the nematodes Aspidodera raillieti, Cruzia tentaculata, Trichuris didelphis and Trichuris minuta in the large intestine; Turgida turgida in the stomach; Travassostrongylus orloffi and Viannaia hamata ; and the trematodes Brachylaima advena and Rhopalias coronatus in the small intestine. Three helminth morphospecies were also recovered: the nematodes Hoineffia sp. and Viannaia sp. and a cestode in the small intestine. Cruzia tentaculata and V . hamata were the species with the highest mean abundances and intensities, while the most prevalent species were A . raillieti, C . tentaculata, T . turgida and V . hamata, forming the central nucleus of the helminth component community. The analysis of the helminth metacommunity structure indicated a Gleasonian pattern for the total set of infracommunities, corroborating the beta diversity indices, which indicated more species replacement than loss between localities and infracommunities, although at a low level. The results indicated a stronger influence of host attributes than geographical distance on the community structure.